A CASE STUDY: STUDENTS-TEACHER SHIFTING ROLES IN THE CLASSROOM AND ITS IMPACT VIS A VIS CHANGING CLASSROOM CLIMATE - Aprianti, Nur (2015)
This study is purposively designed and conducted to investigate and identify the occurrence of shifting roles in the process of teaching and learning activities along with the situation or the classroom climate during the classroom. The study used descriptive-qualitative design, using the framework of Suherdi (2010) and aided by framework from Berry (1981) and Ventola (1988) by using classroom discourse analysis as the tool of data analysis. The main data of this study are collected from four times in-class observation. The data analysis is conducted through video transcription and the identification of categories of exchanges and dominant interactant based on the framework of classroom discourse analysis. The findings reveal that the occurrence of shifting roles indeed happened during the classroom activities, it is also observed that the use of shifting roles can be marked as a pedagogical strategy in teaching learning process that can occur in a specific time and purpose, such as to negotiate, elicit, and sum up students' answer. It also reveals that the shifting roles between students and teacher can be related to the establishment of positive classroom climate and classroom participation. Along the way it is also discovered that role shifting does not only happen between students and teacher as the primary knower, but also happens to the teacher as he is adapting to the classroom situation and the learning objectives. Keywords: Shifting roles, classroom interaction, classroom climate, classroom participation Penelitian ini bertujuan untuk menginvestigasi dan mengidentifikasi kemunculan Shifting Roles dalam proses mengajar belajar serta situasi atau iklim kelas selama pelajaran berlangsung. Desain penelitian ini adalah deskriptif kualitatif menggunakan kerangka dari Suherdi (2010) yang dibantu oleh kerangka dari Berry (1981) dan Ventola (1988), serta menggunakan Classroom Discourse Analysis sebagai alat analisis. Data utama dari penelitian ini diperoleh dari empat kali observasi kelas. Analisis data dilakukan melalui transkripsi video dan identifikasi kategori pertukaran dan Dominant Interactant berdasarkan kerangka Classroom Discourse Analysis. Hasil dari penelitian ini menunjukkan bahwa kemunculan pergantian peran (Shifting Roles) memang terjadi di dalam aktifitas kelas, serta penggunaan Shifting Roles dapat dijadikan sebagai strategi pedagogik dalam proses belajar mengajar yang dapat terjadi dalam waktu dan tujuan tertentu seperti negosiasi, menggali, dan menyimpulkan jawaban siswa. Penelitian ini pun menemukan bahwa pergantian peran (shifting roles) yang terjadi antara siswa dan guru dapat pula dikaitkan dengan partisipasi siswa di kelas dan penciptaan iklim kelas yang positif. Selain itu, ditemukan pula bahwa pergantian peran (shifting roles) tidak hanya terjadi antara siswa dan guru namun pergantian peran (shifting roles) juga terjadi kepada guru ketika guru beradaptasi dengan situasi kelas sesuai dengan tujuan pembelajaran yang ingin dicapai. Keywords: pergantian peran (Shifting roles), interaksi kelas, iklim kelas, partisipasi kelas.